Investigation on cooling efficiency of a 3D-printed integrated inter cooler applicable to a miniature multi-stage compressor. (April 2019) - Deng, Yipan; Miao, Na; Liu, Yinshui; Zhai, Xiaomin; Wu, Defa
Highlights: A miniature multi-stage compressor (MMSC) is proposed. A 3D-printed integrated inter cooler is proposed and fabricated by SLM processing. Simulation investigation on cooling efficiency of the inter cooler is carried out. Effects of sensitive parameters are analyzed. Sufficient cooling of the inter-stage gas can be obtained. Abstract: Inter cooler plays an extremely importance role in improving the volumetric efficiency and isentropic efficiency of multi-stage compressor. For a miniature multi-stage compressor with compact and lightweight structure, conventional inter coolers such as winding copper or stainless steel tubes are incompetent due to their relatively large dimension. A 3D-printed integrated inter cooler with complex channels and compact size is proposed. Selective laser melting process technology is applied due to its high molding precision. A numerical investigation on the cooling efficiency of the inter cooler is carried out. A comprehensive comparison of the overall cooling efficiency is conducted and optimal parameters are obtained for cooling down the inter-stage gas as much as possible. It turns out that sufficient cooling can be obtained when the coolant flow through the inter cooler with a flow rate above 0.2 L/min. Temperature of coolant influences the outlet gas temperature of all stages most significantly.